2010
DOI: 10.2169/internalmedicine.49.2670
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between High-Sensitivity C-Reactive Protein (hs-CRP) and White Blood Cell Count (WBC) as an Inflammatory Component of Metabolic Syndrome in Japanese

Abstract: Objective To compare two systemic inflammatory markers, high-sensitivity C-reactive protein (hs-CRP) and white blood cell count (WBC), as a component of metabolic syndrome (MetS

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 50 publications
3
35
0
Order By: Relevance
“…3 and with MetS in a Japanese health screening population study. 10 In a previous study based on data from 1,062 men and 647 women, we proposed 0.45 mg/L for men and 0.25 mg/L for women as tentative optimal cutoff points of hs-CRP for MetS in Japanese. 18 Subsequently, we proposed 0.40 mg/L for men and 0.35 mg/L for women as the optimal cutoff points of hs-CRP as the inflammatory component of MetS, according to the results of a study of apparently healthy Japanese men (2,185) and women (1,383).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 and with MetS in a Japanese health screening population study. 10 In a previous study based on data from 1,062 men and 647 women, we proposed 0.45 mg/L for men and 0.25 mg/L for women as tentative optimal cutoff points of hs-CRP for MetS in Japanese. 18 Subsequently, we proposed 0.40 mg/L for men and 0.35 mg/L for women as the optimal cutoff points of hs-CRP as the inflammatory component of MetS, according to the results of a study of apparently healthy Japanese men (2,185) and women (1,383).…”
Section: Discussionmentioning
confidence: 99%
“…18 Subsequently, we proposed 0.40 mg/L for men and 0.35 mg/L for women as the optimal cutoff points of hs-CRP as the inflammatory component of MetS, according to the results of a study of apparently healthy Japanese men (2,185) and women (1,383). 10 However, there are some concerns about the reproducibility of the serum levels of hs-CRP, because hs-CRP increases hugely in acute inflammation and the effects continue for several days. Koenig et al suggested that the true association between hs-CRP and cardiovascular risk is underestimated by a single hs-CRP determination, and that serial measurements should be taken.…”
Section: Discussionmentioning
confidence: 99%
“…The longitudinal data from the Framingham Heart Study have clearly shown that individuals with BPs of 120-139/80-89 mm Hg are at increased risk of developing full-blown HT and CVD later in life than individuals with BPs less than 120/80 mm Hg (2). Studies in the United States and other populations have identifi ed an association between increased WBC count and BP (15)(16)(17). The relationship between leukocytes and increased cardiovascular risk is well known.…”
Section: Discussionmentioning
confidence: 99%
“…WBC is an important maker of low-grade systemic inflammation which may be a central mechanism of MetS (22). High sensitive C-reactive protein (hs-CRP) is also a useful marker of systemic inflammation and an independent risk factor of diabetes, cardiovascular disease and MetS (23)(24)(25). It was reported that hs-CPR is superior to WBC as an inflammatory component of MetS (23).…”
Section: Discussionmentioning
confidence: 99%